Der Einfluss von degenerativen Spinalveränderungen auf die Korrelation der peripheren und axialen Knochendichte - Schneider, P.; Börner, W. (Nuklearmedizin - NuclearMedicine, 1994)
Results of bone density measurements by quantitative computed tomography of the peripheral skeleton (pQCT) were compared with those of measurements at the axial skeleton with a view to study the effects of degenerative spinal changes on the validity of bone densitometry of the lumbar spine. 556 consecutive patients were examined by dual-energy x-ray absorptiometry (DXA) of the spine and by peripheral quantitative computed tomography (pQCT) of the distal radius. There were significant differences between the bone mineral values at the distal radius and those at the spine, depending on the degree of spinal degeneration. As expected, spinal degenerations showed a highly significant age dependence. With increasing degeneration the correlations between the radius total bone mineral concentration and the bone density of the lumbar spine decreased from r = 0.45 to 0.23 in women and from r = 0.64 to 0.28 in men. We conclude that the value of spinal DXA is reduced in patients with degenerative spinal disease, compared to the pQCT at the peripheral skeleton.Knochendichtemessungen mit der quantitativen Computertomographie am peripheren Skelett (pQCT) wurden mit Messungen der Knochendichte am Achsenskelett verglichen, um festzustellen, wie degenerative Veränderungen an der Wirbelsäule sich auf die Validität der Knochendichtemessungen an der Lendenwirbelsäule auswirken. 556 aufeinanderfolgende Patienten wurden mit der Zweienergie-Röntgenabsorptiometrie (DXA) an der Wirbelsäule und mit der peripheren quantitativen Computertomographie am Radius untersucht. Wir fanden in Abhängigkeit vom Schweregrad degenerativer Veränderungen signifikante Unterschiede zwischen den Knochendichtewerten am Radius und an der Wirbelsäule. Wie zu erwarten war, zeigten die degenerativen Veränderungen der Wirbelsäule eine hochsignifikante Altersabhängigkeit. Die Korrelationen zwischen der Gesamtdichte am Radius und der Knochendichte der Wirbelsäule nahmen von r = 0,45 auf r = 0,23 bei den Frauen und von r = 0,64 auf r = 0,28 bei den Männern ab. Unsere Ergebnisse zeigen, daß im Vergleich mit der pQCT am peripheren Skelett die DXA bei Patienten mit degenerativen Veränderungen der Wirbelsäule von eingeschränktem Wert ist.
Keywords: Dual-energy x-ray absorptiometry (DXA); peripheral quantitative computed tomography (pQCT); bone density; spinal degeneration; osteoporosis